The Ainu of Northern Japan: Revitalizing a dying Culture - Jónína Huld Björnsdóttir 1997- (2022)
This thesis discusses the strained relationship between the nation of Japan and the Ainu, the indigenous people of northern Japan as well as the Sakhalin and Kurile Isles. Historically a hunter-gatherer society that places great importance on living in harmony with the natural world, the Ainu faced increasing hardships due to the growing influence of the Japanese government in their homelands from the 1600s onward. Centuries of changing policies regarding the Ainu brought their culture to the brink of extinction. While the Ainu still face societal issues and prejudice, their situation has improved greatly. Public awareness and increased legal recognition has invigorated cultural preservation efforts as well as changing the popular views on the Ainu.